2016
DOI: 10.1038/srep25150
|View full text |Cite
|
Sign up to set email alerts
|

Disease-emergence dynamics and control in a socially-structured wildlife species

Abstract: Once a pathogen is introduced in a population, key factors governing rate of spread include contact structure, supply of susceptible individuals and pathogen life-history. We examined the interplay of these factors on emergence dynamics and efficacy of disease prevention and response. We contrasted transmission dynamics of livestock viruses with different life-histories in hypothetical populations of feral swine with different contact structures (homogenous, metapopulation, spatial and network). Persistence pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 46 publications
(66 reference statements)
0
22
0
Order By: Relevance
“…A recent study found that for wild boar, a social species that aggregates in family groups (Podgórski, Lusseau, et al, ; Podgórski, Scandura, et al, ), spatially targeted culling that focuses on removing all members of family groups is more effective than random removal of individuals (Pepin & VerCauteren, ). Although this simulation model did not account for movement responses due to culling, it did include effects of social structuring in disease transmission.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that for wild boar, a social species that aggregates in family groups (Podgórski, Lusseau, et al, ; Podgórski, Scandura, et al, ), spatially targeted culling that focuses on removing all members of family groups is more effective than random removal of individuals (Pepin & VerCauteren, ). Although this simulation model did not account for movement responses due to culling, it did include effects of social structuring in disease transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of these constraints on disease spread across the population will depend on pathogen characteristics, such as transmission route, infectiousness, incubation time, lethality. We can expect highly virulent pathogens with short infectious periods to spread rapidly within groups but have limited population‐level effects, particularly in fragmented or low‐density populations (Ward et al , Pepin and VerCauteren ).…”
Section: Discussionmentioning
confidence: 99%
“…Because different factors may act on each level of social organization (Vander Wal et al ), a hierarchical approach combining analysis of dyadic associations and network‐based metrics, as adopted in our study, offers full understanding of the factors influencing contact heterogeneity (Pepin et al , Vander Wal et al ). Information about contact rates and structure in wildlife populations can be used to parameterize epidemiological models (Craft et al , Pepin and VerCauteren ) and inform disease management to optimize targeted control actions (Grear et al , Hirsch et al ).…”
mentioning
confidence: 99%
“…A recent study found that for wild boar, a social species that aggregates in family groups (Podgórski et al 2014a, Podgórski et al 2014b), spatially-targeted culling that focuses on removing all members of family groups is more effective than random removal of individuals (Pepin & VerCauteren 2016). Although this simulation model did not account for movement responses due to culling, it did include effects of social structuring in disease transmission.…”
Section: Discussionmentioning
confidence: 99%